2019
DOI: 10.3390/ijms20010145
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Human Health

Abstract: Vitamin D is currently one of the hottest topics in research and clinics, as well as in everyday life. Over the past decades, scientists gathered overwhelming evidence indicating that the observed global vitamin D deficiency not only has a negative impact on human skeletal system, but also facilitates development and progression of multiple disease of civilization, including cardiovascular diseases, diabetes, autoimmune disease, and cancer. This Special Issue, entitled “Vitamin D and Human Health”, summarizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 25 publications
1
96
0
15
Order By: Relevance
“…Vitamin D not only plays an essential role in the control of calcium homeostasis and bone mineralization in the human body, but is also related to the occurrence of benign and malignant tumors, infectious diseases, autoimmune diseases, cardiovascular diseases and mental health (Howe & Dellavalle, 2007). The typical forms of vitamin D in the human body are vitamin D2 (VD2, ergocalciferol) and vitamin D3 (VD3, cholecalciferol), which derive from plants and animals (Zmijewski, 2019). The metabolites of these two types of vitamin D are both called 25(OH) D, which is a stable storage form and serum determination marker of vitamin D in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D not only plays an essential role in the control of calcium homeostasis and bone mineralization in the human body, but is also related to the occurrence of benign and malignant tumors, infectious diseases, autoimmune diseases, cardiovascular diseases and mental health (Howe & Dellavalle, 2007). The typical forms of vitamin D in the human body are vitamin D2 (VD2, ergocalciferol) and vitamin D3 (VD3, cholecalciferol), which derive from plants and animals (Zmijewski, 2019). The metabolites of these two types of vitamin D are both called 25(OH) D, which is a stable storage form and serum determination marker of vitamin D in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the important role of vitamin D in the human body, vitamin D deficiency has been widely reported to be associated with many diseases (Zmijewski, 2019). Several studies (Chiang, Natarajan, & Fan, 2016; Degner, 2016; Kinney et al, 2009; Nerhus et al, 2016; Taylor et al, 2016) have shown that vitamin D levels in people with mental illness are generally lower than those in healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D has been associated with positive health benefits due to its effectiveness by playing an essential role in the human endocrine systems such as muscle metabolism, cardio-metabolic risk factor, and inflammation-related cancer [1]. To date, the effects of vitamin D are interested in a variety of researchers, clinicians, and coaches [2]. While considerable evidence supports the effects of vitamin D in research, various researchers are still attempting to find new evidence linking the effect of vitamin D on other health and performance benefits.…”
Section: Introductionmentioning
confidence: 99%
“…These results observed in the Vit.D- group, together with those of prior studies showing a reduction in the glomerular area and an increased fractional mesangial area [14], reflect the presence of an increased number of immature glomeruli in the Vit.D-deficiency models during development. Inverse correlations between nephron number and glomerular size have been previously described in experimental [53] and human [54] studies. Further quantitative analyses through stereologic measurements, such as the length, volume, and/or surface area of the kidney vasculature in both the cortex and the medulla, should be performed to better evaluate this process.…”
Section: Discussionmentioning
confidence: 99%